MICROSTRUCTURAL CHARACTERIZATION OF BIOCHAR–CHITOSAN COMPOSITES LOADED WITH NITROGEN AND Fe FOR SLOW-RELEASE FERTILIZER APPLICATIONS - Martasiana Karbeka; Agnes Lema; Jublina Padalegi (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2026)
Nutrient-use efficiency in agricultural fertilization remains very low because nitrogen is readily lost through leaching and volatilization. Biochar and chitosan can be used as nutrient-coating materials to modify nutrient-release rates and improve fertilization efficiency. This study evaluates the structural and elemental characteristics of chitosan–biochar slow-release fertilizers by comparing BCB@N and BCB@N/Fe composites. Particle size analysis showed an increase in average particle size from 430.18 ± 19.60 µm for BCB@N to 485.48 ± 62.64 µm for BCB@N/Fe. EDX data revealed high percentages of carbon and silica in BCB@N, confirming a porous framework, whereas BCB@N/Fe exhibited elevated oxygen and calcium levels, indicating the formation of Fe–chitosan complexes and the coprecipitation of Ca ions. TEM imaging confirmed that this chemical modification transformed the open internal microstructure of BCB@N into a significantly denser surface in BCB@N/Fe. Accordingly, the smaller particle size and open structure of BCB@N may facilitate faster water diffusion and earlier nutrient release, while the denser structure and larger particle size of BCB@N/Fe may provide a stronger barrier to water diffusion and support slower, more controlled nutrient release.